Comparison of orthologous cyanobacterial aldehyde deformylating oxygenases in the production of volatile C3-C7 alkanes in engineered E. coli - Pekka Patrikainen; Veronica Carbonell; Kati Thiel; Eva-Mari Aro; Pauli Kallio (Elsevier B.V., 2022)
Aldehyde deformylating oxygenase (ADO) is a unique enzyme found exclusively in photosynthetic cyanobacteria, which natively converts acyl aldehyde precursors into hydrocarbon products embedded in cellular lipid bilayers. This capacity has opened doors for potential biotechnological applications aiming at biological production of diesel-range alkanes and alkenes, which are compatible with the nonrenewable petroleum-derived end-products in current use. The development of production platforms, however, has been limited by the relative inefficiency of ADO enzyme, promoting research towards finding new strategies and information to be used for rational design of enhanced pathways for hydrocarbon over-expression. In this work we present an optimized approach to study different ADO orthologs derived from different cyanobacterial species in an in vivo set-up in Escherichia coli. The system enabled comparison of alternative ADOs for the production efficiency of short-chain volatile C3-C7 alkanes, propane, pentane and heptane, and provided insight on the differences in substrate preference, catalytic efficiency and limitations associated with the enzymes. The work concentrated on five ADO orthologs which represent the most extensively studied cyanobacterial species in the field, and revealed distinct differences between the enzymes. In most cases the ADO from Nostoc punctiforme PCC 73102 performed the best in respect to yields and initial rates for the production of the volatile hydrocarbons. At the other extreme, the system harboring the ADO form Synechococcus sp. RS9917 produced very low amounts of the short-chain alkanes, primarily due to poor accumulation of the enzyme in E. coli. The ADOs from Synechocystissp. PCC 6803 and Prochlorococcus marinus MIT9313, and the corresponding variant A134F displayed less divergence, although variation between chain-length preferences could be observed. The results confirmed the general trend of ADOs having decreasing catalytic efficiency towards precursors of decreasing chain-length, while expanding the knowledge on the species-specific traits, which may aid future pathway design and structure-based engineering of ADO for more efficient hydrocarbon production systems.